1 - The International Criminal Court, Justice, Peace and the Fight against Impunity in Africa: An Overview - Mangu, André Mbata (Africa Development, 2021)
The year 2013 marked the fiftieth anniversary of the Organisation of African Unity that was replaced with the African Union (AU). It coincided with a great deal of criticism against the International Criminal Court (ICC) by AU member states that were yet instrumental in its creation and referred most of its cases. Using a combined international law and a political science approach, this article aims to contribute to the debate that has been raging on the ICC since it indicted some African leaders. It holds that although much of the criticism is unfounded, the ICC should gain in terms of legitimacy by improving its operations as an impartial court not subjected to the superpowers within the UN Security Council. Instead of withdrawing from the Rome Statute, African States should also comply with their obligations and cooperate with the ICC from which the majority of their people still expect so much. Based on its human rights record, this article argues that the AU’s attempt to bypass the ICC by establishing an international criminal law section mandated to deal with international crimes within the African Court on Human and Peoples’ Rights is unlikely to end impunity and promote peace on the continent.